2018
DOI: 10.3747/co.25.4014
|View full text |Cite
|
Sign up to set email alerts
|

Computed Tomography–Quantified Body Composition Predicts Short-Term Outcomes After Gastrectomy in Gastric Cancer

Abstract: Background Malnutrition is a common and critical problem that influences outcome in cancer patients. Body composition reflects a patient’s metabolic profile and physiologic reserves, which might be the true determinant of prognosis. In the present study, which aimed to identify valuable new prognostic indicators, we investigated the association between computed tomography–quantified body composition and short-term outcomes after gastrectomy for gastric cancer.MethodsSkeletal muscle index, mean muscle attenuati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
76
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 64 publications
(82 citation statements)
references
References 40 publications
(50 reference statements)
2
76
0
4
Order By: Relevance
“…After title and abstract and full text screening, 15 studies were eligible for inclusion, reporting on 4887 patients ( Figure 1). The association between low muscle mass and postoperative complications was reported in 12 studies [12,13,[23][24][25][26][27][28][29][30][31][32] of which 9 studies reported data on severe postoperative complications (Clavien-Dindo grade ≥III) [12,[23][24][25][26][27][28]31,32]. Overall mortality was reported as an outcome measure in 9 studies [24][25][26]28,31,[33][34][35], and 5 studies reported on disease-specific mortality [28,31,[33][34][35].…”
Section: Study Selectionmentioning
confidence: 99%
See 4 more Smart Citations
“…After title and abstract and full text screening, 15 studies were eligible for inclusion, reporting on 4887 patients ( Figure 1). The association between low muscle mass and postoperative complications was reported in 12 studies [12,13,[23][24][25][26][27][28][29][30][31][32] of which 9 studies reported data on severe postoperative complications (Clavien-Dindo grade ≥III) [12,[23][24][25][26][27][28]31,32]. Overall mortality was reported as an outcome measure in 9 studies [24][25][26]28,31,[33][34][35], and 5 studies reported on disease-specific mortality [28,31,[33][34][35].…”
Section: Study Selectionmentioning
confidence: 99%
“…Most studies were retrospective cohort studies (67%) [12,13,[24][25][26][27][28]31,33,34], although 5 were prospective in nature (33%) [23,29,30,32,35]. The majority of the studies included more men than women, with a percentage of male patients varying from 35% to 84%.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 3 more Smart Citations